ANALISIS KESADARAN, KEJUJURAN DAN KEDISIPLINAN WAJIB PAJAK TERHADAP PENGHINDARAN PAJAK PADA KPP WONOCOLO SURABAYA - Hama, Aloisius (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The purpose of this study is to prove and test awareness, honesty and discipline have a simultaneous and partial effect on tax avoidance.The population in this study were individual taxpayers in Kepuh Sendan Village, Waru District, Sidoarjo Regency who were registered at the KPP Pratama Surabaya Wonocolo. The analysis technique used is multiple linear regression with hypothesis testing, model suitability test and t test.Based on the results of the analysis and testing that has been done, the following conclusions can be drawn: Taxpayer Awareness, Taxpayer Honesty, and Taxpayer Discipline have no simultaneous effect on tax avoidance. Taxpayer Awareness, Taxpayer Honesty, and Taxpayer Discipline have no partial effect on tax avoidance